Factors Affecting Consumers’ Attitude Towards Online Food Delivery Services in Punjab - Satinder Kumar; Sandeep Kumar (LPPM Universitas Duta Bangsa Surakarta, 2022)
In this modern era, advancements in technology have grown rapidly. These advancements have led the e-commerce sector to open new avenues for today’s businesses, especially online food delivery services. E-commerce is the buying and selling of goods and services over the internet. A combination of marketing intelligence and technology has resulted in the development of mobile applications which use the internet as a medium to advertise products and services. The extant research purpose is to examine consumers' attitudes towards online food delivery services in Patiala. To know their opinion, data was collected from online questionnaires, questionnaires were sent through the mail. Data for this empirical study was collected online and analyzed using the SPSS through a structured questionnaire to achieve the objective. The study identified the factors in the adoption of food delivery services and an attempt has been made to position them in the Multi-Dimensional Matrix. Findings of the study that convivence motivation, service, purchase safety, and security, purchase intention, delivery experience, price value, and service quality of food delivered factors are considered to be directly affecting the success of online food delivery services. Information quality perceived comparability, and perceived usefulness is found to be considered indirect factors. Online food ordering is a rapidly growing industry around in India, as well as city of Patiala is at an immature stage. Due to the growth and reach of the Internet as well as the hectic schedule of the consumer, businesses need to identify the need of the customer and deliver food to the doorstep of the consumer. A better understanding of the consumer market will contribute to realizing the full potential of the e-commerce platform as it has the potential to impact the economy, businesses, and the quality of life of the people.